Quản lí hoạt động bồi dưỡng năng lực sư phạm cho đội ngũ giáo viên ở các trường trung học cơ sở huyện Phú Thiện, tỉnh Gia Lai: thực trạng và khuyến nghị - Nguyễn , Thị Then (Tạp chí Giáo dục, 2024)
Fostering pedagogical competence to help teachers increase their level of adaptability to ever-changing professional requirements is considered a very important issue. However, at secondary schools in Phu Thien district, Gia Lai province, activities to foster pedagogical competence for teachers still have many limitations; one of the reasons comes from the management of this activity. Research results show that the management of content, methods, and forms of activities to foster pedagogical competence for teachers at secondary schools in Phu Thien district are evaluated at a good level, bringing positive results; however, testing and assessment activities and conditions to support training activities still have limitations and inadequacies. This situation is the basis for proposing management measures consistent with practice to improve the effectiveness of pedagogical competence training activities for teachers at secondary schools in the research area.